Inflammatory responses of Nile tilapia Oreochromis niloticus to Streptococcus agalactiae: effects of vaccination and yeast diet supplement - Salvador, Rogerio; Toazza, Caroline Silva; Engracia de Moraes, Julieta Rodini [UNESP]; de Moraes, Flavio Ruas [UNESP] (Inter-research, 2012)
This study evaluated the effects of dietary supplementation with 0.3% Saccharomyces cerevisiae yeast cell wall and of vaccination against Streptococcus agalactiae on the cellular component of acute inflammation induced in the coelomic cavity of Nile tilapia Oreochromis niloticus and on survival of the fish after challenge. A total of 84 tilapia of mean (+/- SD) weight 125.0 +/- 1.5 g were distributed among twelve 310 l fiberglass tanks according to a 2 x 2 x 3 factorial design in the following manner: with and without supplementation; 2 stimulations (oily solution without S. agalactiae vaccine and vaccination); 15 d later all fish were intracoelomically challenged with 10(8) CFU ml(-1) of a homologous strain of S. agalactiae, and evaluated after 6, 24 and 48 h, with 7 replicates. The fish received the non-supplemented or supplemented diet for a total of 77 d. The vaccination was performed on the 60th day, intracoelomically, as a single injection of 0.5 ml of the vaccine containing 10(8) CFU ml(-1). Fifteen days later, all the fish were challenged with S. agalactiae by means of an intracoelomic inoculation of 10(8) CFU ml(-1). No mortality was observed among the supplemented fish. The fish that were fed the non-supplemented diet and immunized with the bacterium presented a mortality rate of 28.5%. Among the non-supplemented and non-immunized fish, the mortality rate was 38.09%. Supplementation, in both vaccinated and non-vaccinated fish, induced larger accumulations of thrombocytes, lymphocytes and macrophages at the inflammatory focus. The results suggest that supplementation with 0.3% yeast cell wall, in both vaccinated and non-vaccinated fish, improved the inflammatory response of the fish and protected against the challenge. Vaccination increased the defense response, but the effect was stronger when associated with supplementation with S. cerevisiae.
Keywords: Inflammation; Saccharomyces cerevisiae; Vaccination; Streptococcus agalactiae; Challenge